Project scheduling with multiple modes: A comparison of exact algorithms - Sönke Hartmann; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1997)
This paper is devoted to a comparison of all available branch-and-bound algorithms that can be applied to solve resource-constrained project scheduling problems with multiple execution modes for each activity. After summarizing the two exact algorithms that have been suggested in the literature, we propose an alternative exact approach based on the concepts of mode and extension alternatives to solve this problem. Subsequently, we compare it to the two procedures available in the literature. Therefore, the three algorithms as well as all available bounding criteria and dominance rules are summarized in a unified framework. In addition to a theoretical comparison of the procedures, we present the results of our computational studies in order to determine the most efficient algorithm.
Keywords: 650; Project Management and Scheduling; Multiple Modes; Branch-and- Bound; Bounding Rules; Computational Results